Pengaruh Kepemimpinan, Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. Charoen Pokphand Jaya Farm 12 Tongas Probolinggo - Mayditha, Revilia; Bahri, Mohammad Saiful; Hermanto, Hermanto (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted on PT. Charoen Pokphand Jaya Farm 12 Tongas Probolinggo with the aim of determining the influence of leadership, work motivation, organizational commitment on the performance of PT employees. Charoen Pokphand Jaya Agriculture 12 Tongas Probolinggo. The type of research used is a quantitative approach. The sample in this study was 41 permanent employees. The data sources used in this research come from primary data and secondary data. Data was collected through questionnaires and completed through data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R-Square) and partial tests. The research results show that leadership, work motivation and organizational commitment have a positive and significant effect on employee performance. It can be proven that from the partial test of the leadership variable (X1) the value obtained is tcount (3.198) > ttable (1.687) with sig = 0.003. The work motivation variable (X2) obtained a value of tcount (3.652) > ttable (1.687) with sig = 0.001. And the organizational commitment variable (X3) obtained a value of tcount (4.513) > ttable (1.687) with sig = 0.000.